Failure Law of Soft and Hard Interlayer Overlying Rock in Gently Inclined, Super‐Thick Coal Seam and Research on the Development Height of a Water‐Conducting Fissure Zone - Kaijie Duan; Peilin Gong; Kang Yi; Guang Wen; Hui Kang; Ziyang Feng; Tong Zhao; Peng Li (Energy Science & Engineering, 2025)
ABSTRACT This study examines the failure laws of soft and hard interlayer overlying rocks and the development height of the water‐conducting fracture zone in a gently inclined super‐thick coal seam at the Qifeng coal mine, Shanxi. The overlying rocks above the working face were classified into four typical structural types: soft‐hard‐soft‐hard, hard‐soft‐hard‐soft, soft‐soft‐hard‐hard, and hard‐hard‐soft‐soft. First, the failure laws of these four types of overlying rock structures were studied theoretically. Theoretical analysis revealed that different overlying rock structures form different composite rock beams that move synchronously after coal excavation. Numerical simulation using FLAC3D showed that the overburden failure does not change linearly but forms different combined rock beams according to the different overburden structures, resulting in a step change. The soft–soft–hard–hard overburden structure exhibits the largest damage extent, while the soft–hard–soft–hard overburden structure results in the highest damage height. When the hard rock above the coal seam is closer to the stope, the influence of the mining stress is greater, leading to stress concentration at the junction of soft and hard rocks. Three methods—theoretical analysis, numerical simulation, and field measurement—were used to study the overlying rock failure law and the development height of the water‐conducting fracture zone of the 51408 working face of the Qifeng Coal industry. The results show that the guiding height of the 51408 working face of the Qifeng Coal industry is 120.12, 103.6, 113.2, and 116.1 m for the four overlying rock structures. The maximum measured height of 116.1 m was considered the development height of the water‐conducting fracture zone. The field‐measured results are consistent with those obtained by theoretical calculation and numerical simulation, confirming the accuracy of the theoretical analysis and numerical simulation and providing a basis for water prevention and control of the roof of gently tilting super‐thick coal seams.